Exploring the plutonic-volcanic link: a zircon U-Pb, Lu-Hf and O isotope study of paired volcanic and granitic units from southeastern Australia - Kemp, A.; Hawkesworth, C.; Paterson, B.; Foster, G.; Kinny, Peter; Whitehouse, M.; Maas, R. (Royal Society of Edinburgh, 2008)
The relationship between plutonic and volcanic rocks is central to understanding the geochemical evolution of silicic magma systems, but it is clouded by ambiguities associated with unravelling the plutonic record. Here we report an integrated U-Pb, O and Lu-Hf isotope study of zircons from three putative granitic-volcanic rock pairs from the Lachlan Fold Belt, southeastern Australia, to explore the connection between the intrusive and extrusive realms. The data reveal contrasting petrogenetic scenarios for the S- and I-type pairs. The zircon Hf-O isotope systematics in an I-type dacite are very similar to those of their plutonic counterpart, supporting an essentially co-magmatic relationship between these units. The elevated 18O of zircons in these I-type rocks confirm a significant supracrustal source component. The S-type volcanic rocks are not the simple erupted equivalents of the granites, although the extrusive and plutonic units can be related by open-system magmatic evolution. Zircons in the S-type rocks define covariant Hf-18O arrays that attest to mixing or assimilation processes between two components, one being the Ordovician metasedimentary country rocks, the other either an I-type magma or a mantle-derived magma. The data are consistent with models involving incremental melt extraction from relatively juvenile magmas undergoing open-system differentiation at depth, followed by crystal-liquid mixing upon emplacement in shallow magma reservoirs, or upon eruption. The latter juxtaposes crystals with markedly different petrogenetic histories and determines whole-rock geochemical and textural properties. This scenario can explain the puzzling decoupling between the bulk rock isotope and geochemical compositions commonly observed for granite suites.